The place of philosophy of education and human nature in security management and national development (2018)
One of the several purposes of education is the acquisition of knowledge required to re fine man in terms of behaviour and attitudes. Educational process has as one of its focuses, the affective domain, which is expected to influence man's attitudes, behaviour and character. Several works had been carried out on attitudes of man but not many had been done in the aspect of human nature as a factor that can influence moral behaviours. Philosophy comes handy in the inculcation of right moral actions as its component of axiology, through the aspect of ethics, encourages cultivation of right and good attitudes in interpersonal relations to guarantee security and development of the society. In ensuring this, understanding the nature of man as one of the contents of Philosophy of Education becomes expedient in order to find out good approaches by which thè process of education can build right moral attitudes and actions in man for the purpose of securing and developing the society. This paper attempts to examine in a philosophical discourse, thè place of human nature in cultivating right moral attitudes. It discusses concepts like hedonism, rationalism and virtue. This is to justify the essence of educational process as an instrument per excellence to achieve security and development aspirations of the society. The paper recommends among several others the need to structure contents of each lesson in the classrooms towards acquisition of appropriate social values and virtues that can enable learners become rational in their decision making. It also suggested that a philosophical understanding of the nature of man will enable teachers as well as school counsellors to be more effective in their professional responsibilities. The paper concludes by stating that an understanding of the nature of man and its philosophical implications will enable educators practice their profession efficiently to attain society’s desired goals of secured and developed environment.